Critical Study of National Examination Policy in the Students’ Learning Achievement and its Implications for Madrasah - Aries Musnandar; Sutrisno Sutrisno; Suci Hidayati; Aji Wahyudin; Tajudin Arifin (Yayasan Adra Karima Hubbi, 2024)
Background. The National Examination (UN) policy in Indonesia, which applies to both public schools and Madrasahs, has been criticized for its limitations and lack of alignment with modern educational evaluation concepts. The National Examination is considered inadequate as it lacks multifunctionality and is not suited for evaluating all types of educational institutions. Particularly for Madrasahs, which focus on students' morals and Islamic character, the National Examination is seen as an inappropriate tool for assessment. Purpose. The researcher aims to explore the implications of the National Examination policy for Madrasahs, utilizing a literature review approach. The goal is to evaluate the policy from the perspective of contemporary learning evaluation concepts and determine its fairness, appropriateness, and theoretical grounding. Method. A literature review approach is employed to analyze the National Examination policy and its impact on Madrasahs. This approach involves examining various scholarly sources and theoretical frameworks related to learning evaluation. Results. The study reveals that the National Examination policy is unjust, inappropriate, and lacks a solid theoretical basis. It highlights that the policy, which relies predominantly on written tests (paper & pencil tests), fails to adequately assess the diverse aspects of student learning, particularly in the context of Madrasahs, which emphasize religious education. Conclusion. The findings indicate that the National Examination is not a suitable evaluation tool for Madrasahs and is misaligned with modern educational evaluation theories. The reliance on written tests does not fully capture the holistic nature of student learning, especially in institutions with a focus on religious values. The study calls for reconsideration of the evaluation methods used for Madrasahs to better align with their educational objectives and theoretical foundations.